INDUKSI KALUS TANAMAN KENTANG DOMBU (SOLANUM TUBEROSUM L.) SECARA IN VITRO DENGAN PEMBERIAN ZPT 2,4-D (DICHLOROPHENOXY ACETID ACID) - Idris, Siti RLR; Paserang, Asri Pirade (Univ. Tadulako, 2019)
This research was aimed to determine the effect of the PGR 2.4-D (Dichlorophenoxy Acetid Acid) in various concentrations on induceing callus of Dombu potato (Solanum tuberosum L.). This research was performed based on Completely Randomized Design (RAL) with 6 treatments and 3 times repetation, so there were 18 experiment units. Each experiment used 3 explants so as there were 54 explants. The combination of concentration of the tested PGR in the culture media were T1 = MS0+ 2.4-D 0 ppm (control), T2 = MS0+ 2.4-D 0.5 ppm, T3 = MS0+ 2.4-D 1 ppm, T4= MS0+ 2.4-D 1.5 ppm, T5 = MS0+ 2.4-D 2 ppm and T6 = MS0+ 2.4-D 2.5 ppm. The results showed that callus induction was appeared in the concentration of 1.0, 1.5, 2.0, and 2.5 ppm. Callus was generally formed on the Day-8 after plantation. Callus color was mostly greenish transparent, callus texture was mostly crumb type, and callus formation percentage was almost 100%. The best media for inducing the callus was in treatment T4 (1.5 ppm 2.4-D), it referred to the formed callus biomass